Highly Efficient Asymmetric Multiple Resonance Thermally Activated Delayed Fluorescence Emitter with EQE of 32.8 % and Extremely Low Efficiency Roll‐Off. (15th February 2022) - Liu, Futong; Cheng, Zhuang; Jiang, Yixuan; Gao, Lei; Liu, Hanxuan; Liu, Hui; Feng, Zijun; Lu, Ping; Yang, Wensheng
Abstract: Multiple resonance thermally activated delayed fluorescence (MR‐TADF) emitters show great potentials for high color purity organic light‐emitting diodes (OLEDs). However, the simultaneous realization of high photoluminescence quantum yield (PLQY) and high reverse intersystem crossing rate ( k RISC ) is still a formidable challenge. Herein, a novel asymmetric MR‐TADF emitter (2Cz‐PTZ‐BN) is designed that fully inherits the high PLQY and large k RISC values of the properly selected parent molecules. The resonating extended π‐skeleton with peripheral protection can achieve a high PLQY of 96 % and a fast k RISC of above 1.0×10 5 s −1, and boost the performance of corresponding pure green devices with an outstanding external quantum efficiency (EQE) of up to 32.8 % without utilizing any sensitizing hosts. Remarkably, the device sufficiently maintains a high EQE exceeding 23 % at a high luminance of 1000 cd m −2, representing the highest value for reported green MR‐TADF materials at the same luminescence. Abstract : Using asymmetric peripheral protection as a design motif, two high efficiency and fast reverse intersystem crossing rate multiple resonance thermally activated delayed fluorescence materials were designed and synthesized. The corresponding device exhibits pure green emission with a remarkable external quantum efficiency of 32.8 % and relatively low efficiency roll‐off without utilizing any sensitizer.